Bis‐(p‐hydroxyphenyl)‐pyridyl‐2‐methane (BHPM)—the active metabolite of the laxatives bisacodyl and sodium picosulfate—enhances contractility and secretion in human intestine in vitro. Issue 7 (14th February 2018) - Krueger, D.; Demir, I. E.; Ceyhan, G. O.; Zeller, F.; Schemann, M.
Abstract: Background: Stimulant laxatives are widely used to treat constipation. We investigated in human small and large intestinal preparations the effects of bis ‐(p‐hydroxyphenyl)‐pyridyl‐2‐methane (BHPM), the active metabolite of the laxatives bisacodyl and sodium picosulfate on smooth muscle tone and epithelial secretion. Methods: Circular and longitudinal muscle tone of small or large intestinal preparations were recorded with isometric force transducers. Epithelial ion flux (ISC ) and tissue resistance was measured with Ussing chamber technique after apical and basolateral BHPM application to large intestinal mucosa/submucosa preparations. Studies were performed in macroscopically normal specimens from 79 patients. Key Results: BHPM concentration‐dependently (0.5‐5 μM) increased the tone of circular and longitudinal muscle from small to large intestine. The effect was strongest in large intestinal longitudinal muscle and smallest in small intestinal circular muscle. Increase in muscle tone was prevented by the L‐type Ca ++ channel blocker nifedipine but insensitive to the nerve blocker tetrodotoxin. Apical or basolateral BHPM concentration‐dependently decreased or increased ISC, respectively. The KC a 1.1 (BK) channel blocker iberiotoxin reversed apical ISC decrease whereas tetrodotoxin reversed basolateral ISC increase. BHPM had no effect on tissue resistance or nerve‐mediated secretory or muscle response with one exception: at the highest concentration basolateral BHPM reduced nerve‐mediated secretion. Conclusions and Interferences: BHPM enhanced mucosal secretion and muscle contractility. Results suggested that the laxative effect of BHPM was a consequence of the increase in muscle tone as well as an increased K + secretion when acting luminally and a nerve‐driven Cl − and HCO3 − secretion once acting basolaterally after absorption. Abstract : We identified the action of bis ‐(p‐hydroxyphenyl)‐pyridyl‐2‐methane (BHPM), the active metabolite of the laxatives bisacodyl and sodium picosulfate, in human intestinal samples. BHPM increased muscle tone in small and large intestine. It enhanced K+ secretion when acting luminally and nerve‐driven Cl − and HCO3 − secretion once acting basolaterally after absorption. Increase in muscle activity and epithelial secretion explain the laxative effects of BHPM.